Morphology evolution of primary Mg2Si in Ca-modified Al–Mg2Si alloy with various contents of Mg/Si. Issue 1 (24th November 2021) - Yu, Hong-Chen; Men, Yu-Zhuo; Yang, Shu-Guo; Liu, Hui; Yu, Lei; Xu, Xue-Dong; Li, Yi-Fei; Zou, Chang-Sheng; Wang, Hao-Nan; Zhong, Wei-Rong
Abstract : The combined influence of Mg/Si and Ca contents on the crystallization of primary Mg2 Si in Al–Mg2 Si alloy is investigated. Abstract : The combined influence of Mg/Si and Ca contents on the crystallization of primary Mg2 Si in Al–Mg2 Si alloy is investigated. Embryo formation of primary Mg2 Si can be restricted by the addition of Ca while the restricted effect is weakened by increasing the content of Mg/Si, and content of Ca for over-modification is increased with the increased Mg/Si content. Growth of primary Mg2 Si is encouraged with the increasing content of Mg/Si, while the addition of Ca can restrict the growth rate directionally in Ca-modified Al–Mg2 Si alloy, which leads to the morphology evolution of primary Mg2 Si. The serious inhibition effect on the whole crystallization process of primary Mg2 Si caused by increasing the content of Ca is the main reason for the occurrence of over-modification. Dice-like primary Mg2 Si is prepared successfully in the over-modified alloy for the first time. The tip-growth process of the dice-like primary Mg2 Si is revealed, which is completed by 2-D nucleation growth. The study provides a novel method to control the morphology and particle size of primary Mg2 Si, which can further help understand the crystallization process of the crystal.